Biological monitoring of occupational exposure to inorganic arsenic. Issue 12 (1st December 1999) - Apostoli, P; Bartoli, D; Alessio, L; Buchet, J P
Abstract : OBJECTIVES: This study was undertaken to assess reliable biological indicators for monitoring the occupational exposure to inorganic arsenic (iAs), taking into account the possible confounding role of arsenicals present in food and of the element present in drinking water. METHODS: 51 Glass workers exposed to As trioxide were monitored by measuring dust in the breathing zone, with personal air samplers. Urine samples at the end of work shift were analysed for biological monitoring. A control group of 39 subjects not exposed to As, and eight volunteers who drank water containing about 45 micrograms/l iAs for a week were also considered. Plasma mass spectrometry (ICP-MS) was used for the analysis of total As in air and urine samples, whereas the urinary As species (trivalent, As3; pentavalent, As5; monomethyl arsonic acid, MMA; dimethyl arsinic acid, DMA; arsenobetaine, AsB) were measured by liquid chromatography coupled with plasma mass spectrometry (HPLC-MS) RESULTS: Environmental concentrations of As in air varied widely (mean 84 micrograms/m3, SD 61, median 40) and also the sum of urinary iAs MMA and DMA, varied among the groups of exposed subjects (mean 106 micrograms/l, SD 84, median 65). AsB was the most excreted species (34% of total As) followed by DMA (28%), MMA (26%), and As3 + As5 (12%). In the volunteers who drank As in the water the excretion of MMA and DMA increased (from a median of 0.5 to 5 micrograms/day for MMA and from 4 to 13 micrograms/day for DMA). The best correlations between As in air and its urinary species were found for total iAs and As3 + As5. CONCLUSIONS: To avoid the effect of As from sources other than occupation on urinary species of the element, in particular on DMA, it is proposed that urinary As3 + As5 may an indicator for monitoring the exposure to iAs. For concentrations of 10 micrograms/m3 the current environmental limit for iAs, the limit for urinary As3 + As5 was calculated to be around 5 micrograms/l, even if the wide variation of values needs critical evaluation and application of data. The choice of this indicator might be relevant also from a toxicological point of view. Trivalent arsenic is in fact the most active species and its measure in urine could be the best indicator of some critical effects of the element, such as cancer.